D-Dimer in Local Thrombolytic Therapy with Low Doses of Recombinant Human Tissue-Type Plasminogen Activator (rt-PA) in Patients with Peripheral Arterial Occlusive Disease - Koppensteiner, Renate; Speiser, Wolfgang; Minar, Erich; Ahmadi, Ramazan; Ehringer, Herbert (Thrombosis and Haemostasis, 1990)
The generation of D-dimer was studied in the course of local thrombolytic therapy of peripheral arterial occlusions with low doses of recombinant human tissue-type plasminogen activator (rt-PA) in 7 patients. Intermittent local application of rt-PA resulted in a marked increase in D-dimer exceeding values usually seen after intravenous application of manifold higher doses used in myocardial infarction. The increase in D-dimer was related to the estimated thrombus size (length of the occlusion) and the total dose of rt-PA applied. During local rt-PA infusion 6 of 7 patients maintained plasminogen activator inhibitor capacity (PAI-cap) between 34% and 79% of their corresponding pre-treatment levels; detectable levels of PAI-cap in circulating blood during the procedure did not interfere with the success of therapy.